Esteem of Territory and Country in Puglia (Italy) in Perspective of Sustainable Tourism: The Strategic Experiential Approach. An Apulian Case History - Di Vittorio, Arianna (European Scientific Journal, ESJ, 2017)
The richness of tourism for Italian economy and employment depends on the use of environmental, artistic, historical resources, which the Country has available; but also on the realization of an optimal net of relationships and cooperations with the various regional, provincial and local institutions, based on a unitarian national vision of tourism development. The touristic market has suffered some changes through the years, moving from a mass tourism to the global tourism, in order to get to responsible ecofriendly, sustainable tourism. In a so dynamic background, task of companies operating in this sector is that of interpreting the rising needs of consumers, aiming for quality and organization. This paper’s goal consists of bringing in surface the new perspectives of a tourism focused on the discoveyr of territory and the consequent development of country tourism’ concept. Such trend puts the stress on a necessary interconnection between touristic, territorial marketing and policy of territory’s maintenance and development. In light of the changes that have influenced the relationships between touristic market and its own customers, the paper aims to offer a specific picture of relationship between tourism and sustainability, resting particularly on the marketing tools to give value to territory and supply the development of a sustainable tourism. The paper is supported by a practical case regarding the Manor farm in vineyard “Le Fabriche” located in Maruggio, by the Ionic coast of Salento (Puglia-Italy). Such land hosts some of the best accomodating structures, which manage to fuse together the development of its own economical activity with tradition and the peculiarities of the territory that hosts them.